2004
DOI: 10.1111/j.1423-0410.2004.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII (NovoSeven): addition to replacement therapy in acute, uncontrolled and life‐threatening bleeding

Abstract: In an area where very little data exists, we report the usefulness of rFVIIa. We propose that transfusion replacement should aim to correct coagulopathy before infusion of rFVIIa and that a haematologist/transfusion specialist should be involved in the management of these patients. A prognostically significant coagulopathy scoring system is offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 43 publications
(49 reference statements)
1
69
0
4
Order By: Relevance
“…This is consistent with the emerging understanding that rFVIIa may be more effective when it is administered early in the course of refractory blood loss in the setting of adequate amounts of circulating coagulation factors. [17][18][19] It may also explain why rFVIIa was not efficacious in existing randomized controlled clinical trials in bleeding patients, many of which did not stipulate the presence of adequate amounts of coagulation factors before rFVIIa therapy.…”
Section: Karkouti Et Al Factor Viia In Cardiac Surgery 335mentioning
confidence: 99%
“…This is consistent with the emerging understanding that rFVIIa may be more effective when it is administered early in the course of refractory blood loss in the setting of adequate amounts of circulating coagulation factors. [17][18][19] It may also explain why rFVIIa was not efficacious in existing randomized controlled clinical trials in bleeding patients, many of which did not stipulate the presence of adequate amounts of coagulation factors before rFVIIa therapy.…”
Section: Karkouti Et Al Factor Viia In Cardiac Surgery 335mentioning
confidence: 99%
“…It is also comparable to the response to rFVIIa reported in life-threatening haemorrhage from all causes, where the median response rate is reported as 74% [2][3][4][5][6][7][8]. There have been no large case series or randomised controlled trials on the use of rFVIIa in obstetric haemorrhage.…”
Section: Discussionmentioning
confidence: 61%
“…Action of rFVIIa is dependant on the presence of adequate numbers of circulating platelets and adequate fibrinogen concentration. Previous reports have shown that the improvements in laboratory markers of DIC, by the administration of blood components prior to the administration of rFVIIa, are associated with a better response to rFVIIa treatment [4]. It is also recognised that Table 4 Guidance for the use of rFVIIa in major obstetric haemorrhage (i) Use of rFVIIa should be considered in major obstetric haemorrhage: -which continues despite optimal blood product replacement and obstetric measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations